Eksistensi Bisnis Konter Pulsa di Tengah Persaingan Era Digital - Khadijah, Siti; Luqman, Luqman (Studia Economica : Jurnal Ekonomi Islam, 2024)
Research This research aims to examine the existence of the pulse counter business in the midst of the digital era. competition in the digital era. The focus of the research includes effective business strategies, market opportunities, and challenges faced. Descriptive qualitative method method was used with in-depth interviews, participatory observation, and document analysis at Indra's Pulse Counter in Pontianak. document analysis at Indra's Pulse Counter in Pontianak. The results of this study show the importance of service diversification and utilization of digital technology to improve operational efficiency and competitiveness. The main challenges include competition with digital platforms and declining pulse sales. Research identified that collaboration with telecommunications operators and customer service improvements are key strategies to maintain relevance of the pulse counter business. This research provides important insights into the adaptation of traditional businesses in the digital era, showing that despite the changing technology changes the market landscape, pulse counters remain relevant through service innovation and effective communication with customers. services and effective communication with customers. The findings are expected to can serve as a reference for businesses in designing strategies that are adaptive to technological developments and consumer needs. to technological developments and consumer needs.